Effect of pH on the breeding and larval development of Cardinal tetra, Paracheirodon axelrodi - Lim, Chiao Yen (2013)
This study focused on the spawning, embryonic development and larval rearing of Cardinal tetra, Paracheirodon axelrodi. Matured fish with length ranged from 2.2 - 3.0 cm were used in a ratio of 1 male to 2 females for spawning trials. Water in spawning tanks were prepared at 3 different pH, 6.0, 6.5 and 7.0. Tank with pH 6.5 water produced the highest spawning success, however pH 7.0 has the highest number of larvae hatched. Eggs of P. axelrodi are adhesive and round in shape with diameter ranged from 0.9 - 1.0 mm. Eggs took about 30 hours to hatch at temperature between 25 - 26.5 °C. Various embryonic stages were observed during the embryonic development period. After hatching, the larvae were observed for 40 days until the end of metamorphosis. Size increment observed daily from larvae to juvenile stage. Percentages of survival were recorded. Yolk sac was fully absorbed at 5 days after hatching (DAH) and exogenous feeding started at 6 DAH. The fry reached juvenile stage at 40 DAH evident with iridophores fully pigmented at iris and lateral line.